Development of Teaching Modules Based on Guided Problem Based Learning to Improve Students' Mathematical Spatial Ability - Burhany, Muhammad Amirul Haq; Yuliany, Nur; Sulasteri, Sri (Alauddin Journal of Mathematics Education, 2024)
This study aims to determine the quality and characteristics of Guided Problem Based Learning (PBL) based modules to improve students' mathematical spatial abilities. This research uses the ADDIE model modified by Sugiyono. The steps taken in this research consist of (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The research instruments used were validation sheets, observation sheets of learning implementation using modules, student activity observation sheets, teacher and student response questionnaires, and mathematical spatial ability tests. The validity of the developed module obtained a score of 3.79 (valid). Practicality with the implementation of learning using the module amounted to 1.81 (fully implemented) and the teacher's response was very positive with an average percentage of 89.29% of both analysis results, so the module met the practical criteria. While the effectiveness criteria are obtained from the analysis of student activity observations of 70.19% in the good category, student responses to the module provide a positive response with a percentage of 80.77%, and the results of the math spatial ability test show a percentage of 77.77% so that the effectiveness criteria are met.